Female Sexual Dysfunction Following Pelvic Radiation for Anal Cancer: A Systematic Review. (1st August 2022) - Laden, B; Burt, M; Peters, B; Bloss, J; Cunningham, K; Koontz, B; Hannan, J
ABSTRACT: Introduction: Female cancer patients subjected to pelvic radiation often present post-treatment with genitourinary symptoms. Anal cancer is more common in women, and the mainstays of treatment are radiation and chemotherapy. There is minimal focus in the current literature on the sexual pathophysiology that specifically affects female anal cancer patients as a result of radiation therapy. Assessing the data from existing female anal cancer studies may elucidate the impact of pelvic radiation on female sexual dysfunction (FSD). Objective: To evaluate the current literature on FSD in anal cancer patients who received pelvic radiation without surgical intervention. Methods: A search strategy with concept groups inclusive of female pelvic cancers, FSD, and radiation or radiotherapy was iteratively developed by two librarians, and peer reviewed by a third. We conducted a search of the databases MEDLINE via Pubmed, Embase, Scopus, CINAHL Complete, PsycINFO, and Cochrane CENTRAL. After deduplication, 5, 142 citations were assessed by two independent screeners during the initial title and abstract screening. 4, 488 were deemed to not fit the inclusion/exclusion criteria. Exclusion criteria included: animal studies, feasability studies, secondary research studies, populations that were entirely male or did not separate results by sex, who underwent surgical intervention, or consisted entirely of HIV/AIDS patients. Of the 654 items selected for full-text review we filtered for the word "anal" which resulted in 76 articles to screen at the full-text level. Results: Our search identified 76 papers of which 10 met inclusion criteria, 23 are not yet categorized. Of the included studies, 6 were cross sectional, 3 were prospective longitudinal, and 1 consisted of qualitative interviews. Studies were published from 1996-2021, with the majority (n=8) being published after 2013. While total population of anal cancer patients in each study was small, with 9 out of 10 study populations ≤100 subjects, females comprised the majority of patients without exception. The EORTC QLQ CR38/CR29 was employed in 3 studies while the remaining 7 relied on independent questionnaires or interviews, often utilizing CTCAE grading scale. These 7 studies focused on similar symptoms of FSD after radiotherapy. The most common were dyspareunia, impacting 0.037%-35% of patients (3 studies), vaginal/vulvar pain impacting 10-53% of patients (2 studies), vaginal dryness impacting 7-45% of patients (3 studies), and vaginitis impacting 17-33.3% of patients (3 studies). A major limitation to several studies was the proportion of women who were not sexually active after radiation therapy. Conclusions: Assessing the association between pelvic radiation and FSD in anal cancer patients is challenging due to the lack of detailed, validated sexual function questionnaire data, such as the FSFI. With few studies available on this topic and variability of FSD symptoms between the existing studies, additional research is required to more accurately predict adverse outcomes of anal cancer treatment related to FSD. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: GenesisCare